Scalable Electronic Health Record Management System Using a Dual-Channel Blockchain Hyperledger Fabric † - Kaschel-Carcamo, H (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Communication and information technologies have accelerated the implementation of electronic medical records, but at the same time, have put patient privacy, information security and health data at risk. An alternative to address the problem of security and privacy of medical data is the use of blockchain. Scalability has become one of the biggest challenges facing the development of blockchain-based electronic health records (EHRs). The purpose of this article is to implement and test a scalable blockchain-based EHR management system. For this reason, we present a scalable blockchain-based EHR management architecture. In this paper, we propose an EHR management model based on entities and user roles, adapt, and then implement with Hyperledger Fabric in a two-channel configuration. We develop a prototype in Fabric using a one-and two-channel configuration. We then designed and conducted an experiment to verify the performance of the proposed scheme in terms of scalability improvement. This scalable blockchain-based EHR management solution, such as the Hyperledger Fabric platform, offers a viable alternative to address scalability issues, as well as to protect patient’s privacy and the security of their medical data. © 2023 by the authors.